The social inclusion of waste pickers and the adoption of energy recovery using municipal solid waste as a raw material - Costa, Alexandre Sylvio Vieira da Costa; Araújo, Murilo Ferreira de Araújo (National Journal of City Management, 2023)
Brazil produces more than 79 million tons of municipal solid waste per year, and around 1 million waste pickers work in the recovery of this waste. Brazilian law provides for the social inclusion of these workers with a leading role in waste management. The legislation makes it possible to recover energy from waste, but there is resistance from waste pickers, as these technologies can consume materials that are of value to pickers, such as paper, fabrics and plastics. Based on a bibliographic survey, it is intended to contribute to a better understanding of the phenomena involving the modernization of waste management and the social inclusion of waste pickers.